CHARACTERISTICS ОF INSURANCE COMPANIES’ FINANCIAL STATEMENTS АND THEIR AUDIT - Jovkovic, Biljana Č. (Poslovna ekonomija, 2018)
The specificity of insurance companies stems from the very nature of their business, that is to say risk-taking, that natural and legal entities are exposed to for a compensation in the form of premium i.e. insurance companies’ income. Insurance activity, as a company’s business orientation, produces specificities which are reflected in the display of characteristic positions of its balance sheet and income statement. There are many characteristic positions of these balances which arose from various life and non-life insurance risks that are not inherent in other legal entities. A brief review of balance sheet positions in insurance companies was carried out the paper in order to gain an insight into materially significant balance sheet positions inherent in insurance companies. Independent audit should pay special attention and focus additional dose of professional skepticism precisely towards these characteristic positions. Features of auditing process in insurance companies are presented in the last title of the paper. Key words: financial statements, balance sheet, income statement, financial statement audit, the auditor’s opinion.